2023
DOI: 10.1007/jhep06(2023)011
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing complex Langevin for real-time gauge theories with an anisotropic kernel

Abstract: The complex Langevin (CL) method is a promising approach to overcome the sign problem that occurs in real-time formulations of quantum field theories. Using the Schwinger-Keldysh formalism, we study SU(Nc) gauge theories with CL. We observe that current stabilization techniques are insufficient to obtain correct results. Therefore, we revise the discretization of the CL equations on complex time contours, find a time reflection symmetric formulation and introduce a novel anisotropic kernel that enables CL simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Previous studies of SU(2) theory in thermal equilibrium in 3+1 dimensions showed that usual CL simulations often converge to wrong values [36]. Exploiting the kernel freedom of CL, a new anisotropic kernel was introduced in [37] that improves the stability of the stochastic Langevin process and leads to correctly converged results on complex time paths. By going to real times, the CL method with the new kernel has the potential to allow us to extract transport coefficients in QCD directly and eventually to study the non-equilibrium dynamics of QCD from first principles.…”
Section: Further Recent Approaches To Initial Stagesmentioning
confidence: 99%
“…Previous studies of SU(2) theory in thermal equilibrium in 3+1 dimensions showed that usual CL simulations often converge to wrong values [36]. Exploiting the kernel freedom of CL, a new anisotropic kernel was introduced in [37] that improves the stability of the stochastic Langevin process and leads to correctly converged results on complex time paths. By going to real times, the CL method with the new kernel has the potential to allow us to extract transport coefficients in QCD directly and eventually to study the non-equilibrium dynamics of QCD from first principles.…”
Section: Further Recent Approaches To Initial Stagesmentioning
confidence: 99%
“…Details on the derivation of the CL formalism and the drift term on general complex time contours can be found in our recent work [3].…”
Section: Complex Langevin On the Latticementioning
confidence: 99%
“…This allows the transformation of the drift and the noise term without altering the stationary solution of the stochastic differential equation, but it can drastically improve the stability of the dynamics [14,15]. In particular, we apply the anisotropic kernel that is motivated by a contour parametrizationdependent CL formulation and was derived in our earlier paper [3]. This kernel effectively rescales…”
Section: Instabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this, we adopt the methodology introduced in [5], which relies on the equipartition of the chromo-electric and -magnetic fields within the confined phase of QCD. This work is mainly motivated by complex Langevin simulations of Yang-Mills theory for real-time observables [6,7] where increasing the lattice anisotropy has been shown to systematically improve stability [8,9]. This may open the door for calculating real-time observables and the QCD equation of state at finite density, which suffer from severe sign problems and currently impede direct calculations.…”
Section: Introductionmentioning
confidence: 99%